2015
DOI: 10.1002/hbm.22883
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor deficits predict recovery in patients with disorders of consciousness: A preliminary multimodal [11C]Flumazenil PET and fMRI study

Abstract: Objectives: Disorders of consciousness (DoC)-that is, unresponsive wakefulness syndrome/ vegetative state and minimally conscious state-are debilitating conditions for which no reliable markers of consciousness recovery have yet been identified. Evidence points to the GABAergic system being altered in DoC, making it a potential target as such a marker. Experimental design: In our preliminary study, we used [ 11 C]Flumazenil positron emission tomography to establish global GABA A receptor binding potential valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
(68 reference statements)
0
10
0
1
Order By: Relevance
“…It could be speculated that the ECN constitutes a crucial neural substrate of the global workspace that enables consciousness control. Moreover, it has been suggested that the reduced functional connectivity between the DLPFC and precuneus enables the former a popular therapeutic target for non-invasive brain stimulation in prolonged DoC as to restore the disrupted balance between the ECN and DMN (Qin et al, 2015b;O'Neal et al, 2021).…”
Section: Executive-control Network (Ecn)mentioning
confidence: 99%
“…It could be speculated that the ECN constitutes a crucial neural substrate of the global workspace that enables consciousness control. Moreover, it has been suggested that the reduced functional connectivity between the DLPFC and precuneus enables the former a popular therapeutic target for non-invasive brain stimulation in prolonged DoC as to restore the disrupted balance between the ECN and DMN (Qin et al, 2015b;O'Neal et al, 2021).…”
Section: Executive-control Network (Ecn)mentioning
confidence: 99%
“…Then, during nuisance signal regression, 6 head motion-related regressors and the average signals from the CSF and white matter were regressed out 17 , 30 , 31 . After the PCC seed was chosen, the PCC seed-based functional connectivity map was acquired.…”
Section: Methodsmentioning
confidence: 99%
“…The technique allowed to correctly identify 93% of MCS patients and correctly predict consciousness recovery in 74% of patients with disorders of consciousness [ 27 ]. In the same line, a preliminary study in patients with disorders of consciousness using [ 11 C ] Flumazenil PET reported reduced global GABA-A receptor binding and decreased local-to-global ratio in the supragenual anterior cingulate that correlated with behavioral improvement after three months [ 52 ].…”
Section: Neuroimaging In the Assessment Of Diagnosis And Prognosismentioning
confidence: 99%